2009
DOI: 10.1080/07420520902892433
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Maternal Effects on Endogenous Rhythms in Precocial Birds

Abstract: Development involves interactions between genetic and environmental influences. Vertebrate mothers are generally the first individuals to encounter and interact with young animals. Thus, their role is primordial during ontogeny. The present study evaluated non-genomic effects of mothers on the development of rhythms of precocial Japanese quail (Coturnix c. japonica). First, we investigated the influence of mothering on the ontogeny of endogenous rhythms of young. We compared circadian and ultradian rhythms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Similar results have been described in migratory birds (Gwinner, 2003), what we recently discussed in detail in the previous publication (Piesiewicz et al, 2012b). The mechanisms underlying ''photoperiodic memory'' are still unknown, but epigenetic factors, such as maternal behavior, may influence the rhythmic phenotype of the offspring (Formanek et al, 2009;Janczak et al, 2007;Piesiewicz et al, 2012b). Moreover, it was showed that in chickens unpredictable food access caused seemingly adaptive responses in feeding behavior and this changed behavior was then transmitted to the offspring by epigenetic mechanisms (Natt et al, 2009).…”
Section: Discussionsupporting
confidence: 74%
“…Similar results have been described in migratory birds (Gwinner, 2003), what we recently discussed in detail in the previous publication (Piesiewicz et al, 2012b). The mechanisms underlying ''photoperiodic memory'' are still unknown, but epigenetic factors, such as maternal behavior, may influence the rhythmic phenotype of the offspring (Formanek et al, 2009;Janczak et al, 2007;Piesiewicz et al, 2012b). Moreover, it was showed that in chickens unpredictable food access caused seemingly adaptive responses in feeding behavior and this changed behavior was then transmitted to the offspring by epigenetic mechanisms (Natt et al, 2009).…”
Section: Discussionsupporting
confidence: 74%
“…In addition, epigenetic and specifically maternal effects can alter endogenous rhythmicity. For example, in quails the circadian phenotype of the mothers can predict that of their young [36]. Finally, as already mentioned above, after-effects of previous environmental exposure may affect circadian period length t [28], for example, depending on the amplitude and length of the photoperiod an animal experiences [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…When the quail were 3 wks old, they were caged individually in soundproof rooms in order to record their endogenous feeding rhythmicity under DD. The procedure is described in Guyomarc'h and Guyomarc'h (1994) and rhythms analysis in Formanek et al (2009). We then selected circadian rhythmic (R) and circadian arrhythmic (A) individuals for reproduction.…”
Section: Selection Procedures Of the R-and A-linesmentioning
confidence: 99%
“…Japanese quail maintained in constant darkness (DD) display freerunning feeding activity rhythms with a large interindividual variability of rhythmicity level; some quail express a robust circadian and/or ultradian rhythm, whereas others express a noisy rhythm, or no rhythm at all (Formanek et al, 2009;Guyomarc'h et al, 1998;Lumineau et al, 2001). Performing a divergent selection based on the level of circadian rhythmicity in DD, we obtained two distinct lines of quail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation